Text Mining of Airbnb Reviews: A holistic approach on reviewers’ opinions and topics distribution - Rodrigues, Ana Catarina Guinote Fernandes Alves (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence